(untitled) (Modern information system and technologies, 2018)
In the article considered the features of common using multi-frequency signals based on N-OFDM (OFDM) and the expansion method of the spectrum of FHSS. Based on the analysis of the characteristics and properties of existing methods, it has been defined advantages and disadvantages of these methods, and also the ability to withstand barriers. Practical implementation is shown on an example of Bluetooth specification. The introduction of Massive-MIMO technology is proposed in order to increase the bandwidth of the telecommunication system. The article gives recommendations for increasing the number of subscribers who work simultaneously in the common frequency band, or the growth rate of transmission at a constant number of subscribers.